Levantamento das condições de habitabilidade e caracterização higrométrica de edifícios de pequeno porte no Nordeste de Portugal - Luso, Eduarda (2018)
As a result of the permanence of people, mainly elderly and not only, in the interior spaces of old buildings situated in strict climatic zones, both rural and urban, has been a greater concern with the thermal comfort and air quality inside. This concern is fundamentally based on improving the living conditions of residents in order to avoid abandonment and to arouse their interest in them, since these areas are often areas of great tourist interest that need to be preserved and kept alive. In spite of the enormous evolution of thermal energy conservation systems and control of indoor air quality in construction, as well as of the regulations governing its implementation, the ancient buildings do not follow this evolution, presenting a thermal and hygrometric behaviour that sometimes can compromise the comfort, health and activities of its users. This article intends to characterize the inside habitability conditions of sixteen buildings located in the historic centre of Bragança, more precisely in the city's Citadel, buildings characterized by being small, with little natural light and rarely subject to thermal rehabilitation work . It is also intended to compare with the results obtained in 2012 with a similar study and to verify the influence of the programs of incentive to the rehabilitation that have arisen in the meantime. In this way, were analysed the main parameters of hygrometrical nature inside inhabited buildings, chosen at random, such as: temperature and relative humidity, as well as the state of degradation of the building and the existence of pathologies both outside and inside.